UPAYA PENINGKATAN KEPUASAN KONSUMEN MELALUI STRATEGI WORD OF MOUTH MARKETING PADA STUDIO S.A. BEAUTY SPACE SINTANG - Evy Ratnasari (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2025)
This study aims to analyze the efforts of S.A. Beauty Space Sintang in increasing customer satisfaction through the implementation of Word of Mouth (WOM) marketing strategies. The research uses a qualitative descriptive method with data collected through interviews, observation, and documentation. The findings show that although S.A. Beauty Space provides informative social media content and quality service, customer interaction remains relatively low. WOM occurs mostly through private communication rather than public reviews. Customers are satisfied with services, especially during festive events, and often return. The company attempts to respond quickly to customer feedback and uses Instagram to expand brand awareness. Despite the lack of formal programs to optimize WOM, organic testimonials and influencer partnerships help promote the brand. This study concludes that enhancing digital interaction and feedback response is essential to leverage WOM marketing effectively.